The role of vision in maintaining stroke synchronization in K2 crew-boat kayaking - Kong, P. W.; Tay, C. S.; Pan, J. W. (Frontiers in Sports and Active Living, 2020)
This study investigated the role of vision in maintaining stroke synchronization in crew-boat sprint kayaking. Sixteen sprint kayakers from a national team were paired into eight two-seater (K2) crews. Each crew paddled at high intensity with the back paddler`s eyes open or closed in a randomized order. Using video analysis, stroke synchronization was quantified by the timing offsets between the front and back paddlers at four key positions of the stroke. All crews could paddle continuously without capsize or stopping under both visual conditions. In the absence of vision, neither 200-m performance time (p = 0.23, d = 0.47, small effect size) nor stroke rate (p = 0.41, d = 0.31, small effect size) was severely affected. There were no significant effects of vision on stroke synchronization offsets between the front and back paddlers across all key positions (all p > 0.05). Highly skilled paddlers likely relied on the kinesthetic perception to maintain the boat synchronization when visual information was not available.